The Eco-Theological Significance of Ata Long: Constructing Local Wisdom as a Response to Indonesia’s Environmental Degradation - Juhani, Sefrianus; Jebadu, Alexander; Wea, Teofanne Nurinik (Journal of Asian Orientation in Theology, 2026)
Indonesia is experiencing environmental degradation across multiple sectors. This degradation is driven by economic pressures and intensified by an anthropocentric paradigm that places humans at the center of creation. Such a paradigm weakens the spiritual relationship between humans and the natural world. Mitigation efforts often prove ineffective because they overlook local cultural values that sustain ecological balance. This article examines the concept of Ata Long in Manggarai culture as a source of ecological wisdom. The study employs an ethnographic method. Data were collected through in-depth interviews and field observations. Informants were selected using purposive sampling. Data analysis was conducted using a contextual theological approach, which integrates Catholic teaching with the local Manggarai cosmology. The findings show that Ata Long views humans as “guests on earth.” This concept affirms a reciprocal relationship between humans and other creatures. It also rejects human domination over nature. The study further reveals that human well-being is directly linked to environmental sustainability. The ecological-theological values embedded in Ata Long enrich Catholic ecotheology through a relational and inclusive perspective. In conclusion, Ata Long offers a locally rooted theological model that is relevant for addressing environmental crises in Indonesia.